(untitled) (Research, Society and Development, 2023)
The aim of this study was to point out palliative care and the nurse’s perception of cancer patients. This is an integrative literature review with a qualitative approach. Data collection took place through the SCIELO and LILACS database, using the Boolean operator “AND”, library. The results were analyzed using the Minayo method and had as inclusion criteria articles published between 2018 and until November 2022, the last five years, with languages in Portuguese, English and Spanish, the exclusion criteria were incomplete articles, course conclusion work (TCC) or that does not match the research and does not answer my problem. According to the study’s findings, it is noted that professionals refer to palliative care as the one that offers comfort and pain relief, evidencing greater proximity between nursing and the patient and family, who experience strong emotions and a burden high stress. It was found in the search. It proves the need for protocols, humanization, qualification and psychological support for professionals who deal with terminally ill patients in order to improve this practice.